Uncaria tomentosa in the treatment of the herpes labialis: randomized double-blind trial - Caldas, Luiz Querino A.; Olej, Beni; Slomp, Helvo; Timóteo, Margareth O.; Velarde, Luiz Guilherme; Duarte, Hélio; Rosati, José Luiz R.; Moreno, Silvana R.F; Silva, Lívia Maria L.; Destêrro, Verônica de Paula do; Valle, Fernanda M.; Serra, Thiago O. (Brazilian Journal of Sexually Transmitted Diseases, 2010)
Introduction: the lesions caused by herpes simplex are common and have symptoms affecting the quality of life of affected people. Objective: this study aims to assess the safety efficacy of cream with Uncaria tomentosa (cat’s claw), for topical treatment of the herpes labialis. Methods: a clinical investigation was undertaken by means of controlled, randomized, double-blinded protocol in humans. According to the regulatory procedures, 74 patients were selected based on inclusion/exclusion criteria previously submitted to the Local Ethical Committee (no 144/02) whenever herpes labialis lesion appeared. Following, those selected through medical evaluation received either the test (Uncaria) or the reference (Acyclovir) drug. Results: fifty-four episodes of herpes labialis lesions ecloded in 31 volunteers. After their clinical assessment, one showed 4 episodes, two had 3 episodes and six had 2 infections. Hence, 27 patients received the reference drug while 27 applied the Uncaria cream four times a day. Overall, there were not significant differences between either responses. Although, the Uncaria group showed lower scores on the first two days of treatment (p < 0,005; t = 0,028), on day 3, it was even to Acyclovir. Conclusion: the assessment of clinical efficacy of either treatment demonstrated that both drugs were safe as no adverse reactions were reported. Futher, there was no difference (p > 0,05) in the overall period infections as well as in the inflammatory process or crost formation. Regarding the severity of inflammatory reaction, the clinical efficacy of Uncaria tomentosa was significantly better than acyclovir. Rather than the being antiviral drug, the Uncaria tomentosa may act as an anti-inflammatory agent and this would possibly represent an advantage of not inducing viral resistance for long use.